(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The performance of artist-teachers and artist-teachers in the scope of basic education has revealed new attitudes towards understanding the aesthetic act in artistic and pedagogical practice, in the dimension of (re)invention of classroom poetics. In this research, concepts such as the artistic act, the teaching act, incompleteness and non-indifferent thinking were worked on to understand the processes of construction of the aesthetic act, from the perspective of the Dialogical Analysis of Discourse in Bakhtin. Sayings of an artist-teacher and a student were analyzed on the singularization of the subject in the artistic processes in the classroom and its relations with the aesthetic and cultural aspects. The results showed that the organization of artistic actions, arising from aesthetic experiments, which included situations of everyday life, the interrelation between people, objects, their selections and groupings were fundamental to synthesize aspects of artistic creation the or life lived.